Impact of sarcopenia and phase angle on mortality of the very elderly. Issue 1 (16th November 2022) - Kwon, Young Eun; Lee, Jung Sun; Kim, Jee‐young; Baeg, Song In; Choi, Hye Min; Kim, Hong‐Bae; Yang, Joon Young; Oh, Dong‐Jin
Abstract: Background: Sarcopenia is a major component of geriatric syndrome and associated with poor clinical outcomes and mortality. However, diagnosing sarcopenia in the very elderly is difficult, and data on its epidemiology and devastating effects in this group are scarce. Phase angle (PA) is measured using bioimpedance spectroscopy and known to reflect cellular integrity and health. This study aimed to clarify the impact of sarcopenia and PA on mortality risk in very elderly people living in long‐term care facilities. Methods: This prospective cohort study enrolled elderly residents living in nine long‐term care facilities. We collected the participants' data, such as body mass index (BMI), comorbidities and laboratory data, from September to October 2017 and mortality data until October 2019. Nutritional status was evaluated using the Mini Nutritional Assessment (MNA) score, and multifrequency bioimpedance spectroscopy was used to assess body composition including PA. Appendicular skeletal muscle mass was calculated using the body composition monitor‐derived equation of Taiwan's researchers. Sarcopenia was diagnosed using the European Working Group on Sarcopenia in Older People 2 (EWGSOP2) definition (sarcopenia vs. normal group). We divided the participants into two groups according to the median PA value of 3.65° (high vs. low group) and performed multivariate regression analyses to verify the association with mortality risk according to sarcopenia diagnosis or PA group. Results: A total of 279 elderly participants were enrolled; of them, 238 (85.3%) were diagnosed with sarcopenia according to EWGSOP2 guidelines. The median patient age was 83 years, 211 (75.6%) were female and the median BMI was 20.4 kg/m 2 . The sarcopenia group was older than the normal group (84 vs. 81 years; P  = 0.002), had a lower mean BMI (19.8 vs. 26.6 kg/m 2, P  < 0.001) and had a lower MNA score (9 vs. 12 points, P  < 0.001). Sarcopenia was associated with a higher mortality risk after the adjustment for age, sex and diabetes mellitus (hazard ratio [HR], 3.744; 95% confidence interval [CI], 1.155–12.134; P  = 0.028). A low PA was associated with sarcopenia, older age, female sex, low MNA score and overhydration volume; it was also a significant predictor of mortality after the adjustment for age, sex, diabetes mellitus and MNA score (HR, 0.593; 95% CI, 0.420–0.837; P  = 0.003). Conclusions: Sarcopenia is prevalent among the very elderly patients in long‐term care facilities. Sarcopenia and low PA are significantly associated with higher mortality risk.